Monitoring Kependudukan Lahir, Mati, Datang, dan Pindah pada Kelurahan Semper Barat Menggunakan Tableau Public - Riziq, Muhammad Abdul; Nayoan, Vallen Ezra Piter; Lestari, Wida; Wahyudi, Tri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Accurate and up-to-date population data is essential for development planning, decision-making, and improving the quality of public services. However, population data management in Semper Barat Subdistrict still faces challenges such as reporting delays and the lack of data utilization for more precise analysis and policies. Therefore, this study aims to develop a population monitoring system using Tableau Public to visualize data on births, deaths, arrivals, and migrations. The methodology includes data collection and processing, interactive dashboard design, and data visualization implementation using bar charts and line charts with filters based on neighborhood units (RW) and years. The results indicate that Tableau Public enhances efficiency in presenting population information, aids in identifying demographic trends, and supports data-driven decision-making. With this system, population management in Semper Barat Subdistrict is expected to become more transparent and responsive to ongoing social dynamics.